2020
DOI: 10.3390/min10030216
|View full text |Cite
|
Sign up to set email alerts
|

Using Time-Series Videos to Quantify Methane Bubbles Flux from Natural Cold Seeps in the South China Sea

Abstract: Natural cold seeps are an important source of methane and other greenhouse gases to the ocean and atmosphere in the marine environment. Accurate quantification of methane bubble fluxes from cold seeps is vital for evaluating their influence on the global methane budget and climate change. We quantified the flux of gas bubbles released from two natural cold seep sites in the South China Sea: one seep vent in the Haima cold seeps (1400 m depth) and three seep vents at Site F (1200 m depth). We determined bubble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The study of the release of methane from thermogenic and biogenic seeps in the world's oceans (and lakes) has expanded from simple recognition of the extent of the sources to efforts to characterize methane release mechanisms and quantify fluxes. These efforts include studies of: the exchange across the sediment water interface (Tryon and Brown, 2004;Kastner and MacDonald, 2006), bubble fluxes using bottom imaging (Leifer and MacDonald, 2003;Leifer, 2010;Thomanek et al, 2010;Römer et al, 2019;Di et al, 2020;Johansen et al, 2020), bubble fluxes using acoustic imaging (Weber et al, 2014), dissociation of hydrates (Lapham et al, 2010;Lapham et al, 2014), and inferred fluxes to the seafloor based on shallow thermal gradients (Smith et al, 2014). We now know that methane bubble release rates can vary on time scales of seconds, minutes, hours, and days (e.g., Greinert 2008;Leifer, 2019 (and references therein); Johansen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the release of methane from thermogenic and biogenic seeps in the world's oceans (and lakes) has expanded from simple recognition of the extent of the sources to efforts to characterize methane release mechanisms and quantify fluxes. These efforts include studies of: the exchange across the sediment water interface (Tryon and Brown, 2004;Kastner and MacDonald, 2006), bubble fluxes using bottom imaging (Leifer and MacDonald, 2003;Leifer, 2010;Thomanek et al, 2010;Römer et al, 2019;Di et al, 2020;Johansen et al, 2020), bubble fluxes using acoustic imaging (Weber et al, 2014), dissociation of hydrates (Lapham et al, 2010;Lapham et al, 2014), and inferred fluxes to the seafloor based on shallow thermal gradients (Smith et al, 2014). We now know that methane bubble release rates can vary on time scales of seconds, minutes, hours, and days (e.g., Greinert 2008;Leifer, 2019 (and references therein); Johansen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These cold seeps might help our understanding of the dynamics and the environmental impacts of hydrocarbons [ 3 ]. Di et al determined size distribution, bubble release rate, and bubble diameters using a semiautomatic bubble-counting algorithm and observed that the Haima cold seeps in the South China Sea may be a source of methane for the ocean [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a single seepage point just releases 4.8 bubbles per second, each bubble is about 3.25 mm in diameter, and the corresponding gas flux is only 6.75 mL/min. 22 Such a low gas flow rate cannot meet the requirement for a BFEH system to work. To enhance the gas-intake rate of a BFEH system, it is possible to enable an accumulation of low-gas-flux bubbles collected over a long period to pass through it in a short time period.…”
Section: ■ Introductionmentioning
confidence: 99%